Zakharov–Kuznetsov-type limit for ion dynamics system with external magnetic field in R3. (May 2021) - Pu, Xueke; Rong, Rong
Abstract: We consider the Zakharov–Kuznetsov-type limit for ion dynamics system in R 3 with external magnetic field and derive the 3D ZK-type equation from ion dynamics system by Gardner–Morikawa transforms. By making energy estimate for the remainders system we prove that the solutions of the Euler–Poisson system converge globally to ZK-type equation when ε → 0 in 3D.